2018
DOI: 10.1159/000493716
|View full text |Cite|
|
Sign up to set email alerts
|

Role of miR-148a in Mitigating Hepatic Ischemia-Reperfusion Injury by Repressing the TLR4 Signaling Pathway via Targeting CaMKIIα in Vivo and in Vitro

Abstract: Background/Aims: Hepatic ischemia-reperfusion (I/R) injury, which is mainly induced by inflammation and unstable intracellular ions, is a major negative consequence of surgery that compromises hepatic function. However, the exact mechanisms of liver I/R injury have not been determined. Positive crosstalk with the Ca2+/CaMKII pathway is required for complete activation of the TLR4 pathway and inflammation. We previously found that miR-148a, which decreased in abundance with increasing reperfusion tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…Previous studies have found that excessive CaMKIIα is associated with a variety of symptoms, including aggravating hepatic ischemia–reperfusion (I/R) damage 10 and participating in the induction of apoptosis in bone cells 33 and neurons. 9 We also found that the overexpression of Rbfox-1 and CaMKIIα was closely related to neuronal death and degeneration, as well as to neurological damage following ICH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that excessive CaMKIIα is associated with a variety of symptoms, including aggravating hepatic ischemia–reperfusion (I/R) damage 10 and participating in the induction of apoptosis in bone cells 33 and neurons. 9 We also found that the overexpression of Rbfox-1 and CaMKIIα was closely related to neuronal death and degeneration, as well as to neurological damage following ICH.…”
Section: Discussionmentioning
confidence: 99%
“…68 A large number of studies have shown that CaMKIIα is involved in and mediates neuronal death in cerebral ischemia and poisoning (fluorosis), which leads to damage of the nervous system. 912…”
Section: Introductionmentioning
confidence: 99%
“…A previous study suggests that the toll-like receptor (TLR) pathway is linked with the activation of CaMKII in a model of myocardial infarction (Singh et al, 2012). Recently, Wu and collaborators demonstrated that miR-148a attenuates ischemia/reperfusion injury in liver, once CaMKIIα represses the TLR4 signaling pathway in vivo and in vitro, decreasing the production of pro-inflammatory factors (Zheng et al, 2018). Moreover, activation of CaMKII in macrophages is initiated by a significant trigger elevation of intracellular Ca 2+ .…”
Section: The Role Of Camkii In Cardiorenal Syndromementioning
confidence: 99%
“…complex mechanisms are involved in HIRI and studies indicate that Kupffer cells (Kcs), which are liver-resident macrophages, play a crucial role in the inflammatory response in several hepatic diseases (3)(4)(5)(6). Two well-known KC phenotypes, M1 and M2, have different functions in HIRI; M1-polarized Kcs exacerbate IR-induced damage to the liver by producing proinflammatory cytokines such as TNF-α and interleukin (IL)-1β, while anti-inflammatory cytokines, such as IL-10 and TGF-β, are produced by M2-polarized Kcs and protect hepatocytes against IR injury (7)(8)(9). Therefore, increasing the number of M2 cells or reducing the M1 phenotype of Kcs may help to ameliorate HIRI.…”
Section: Introductionmentioning
confidence: 99%